2021
DOI: 10.7759/cureus.19964
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Dysphagia in a Patient Diagnosed Later With Dermatomyositis: A Case Report

Abstract: Dysphagia has been reported in 10%-73% of patients with dermatomyositis. We present the case of a 58year-old female patient who presented to the emergency department of Peterborough City Hospital with acute-onset difficulty in swallowing. Physical examination demonstrates proximal muscle weakness of the upper limbs and symmetrical skin rash over the face, chest, and thighs. Both clinical and laboratory findings pointed towards the diagnosis dermatomyositis. Oesophagogastroduodenoscopy identified no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Persistent complaints of dysphagia in such patients of dermatomyositis might be considered for IV immunoglobulins infusion or other second-line immunosuppressants [ 12 ]. A recent research study utilizing both videofluoroscopic swallow study (VFSS) and manometry concluded that dysphagia observed in patients with inflammatory myopathy is primarily caused by weakened pharyngeal muscle contractions, which is linked to the weakness of the suprahyoid muscles [ 13 ]. Therefore, swallowing rehabilitation therapies like oropharyngeal exercises and compensation techniques would be more effective in managing the condition [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent complaints of dysphagia in such patients of dermatomyositis might be considered for IV immunoglobulins infusion or other second-line immunosuppressants [ 12 ]. A recent research study utilizing both videofluoroscopic swallow study (VFSS) and manometry concluded that dysphagia observed in patients with inflammatory myopathy is primarily caused by weakened pharyngeal muscle contractions, which is linked to the weakness of the suprahyoid muscles [ 13 ]. Therefore, swallowing rehabilitation therapies like oropharyngeal exercises and compensation techniques would be more effective in managing the condition [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The clinical manifestations of dysphagia vary across patients with DM, making the diagnosis and management challenging. Studies have reported that dysphagia can present as an initial symptom, 8,9 or occur progressively over the course of the disease. 10,11 To date, dysphagia in patients with DM remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%